Study the Situation of palm borers in some orchards of Karbala by using different kind of traps . - الجمالي, ناصر عبد الصاحب; الكريطي, عذراء عقيل هادي (Journal of Kerbala for Agricultural Sciences, 2015)
This study was conducted in some palm planting regions at Husseinia and Aoun / Karbala during 2013-2014 to know the presence of palm borers species , dominant species and its population density, it used different kind of traps and evaluated the efficiency of these traps in attracting of palm stalk borers Oryctes elegans .The results indicated that four species palm borers were found , stem borer with long horn (Jebusea hammerschmidti ), stalk borer (Oryctes elegans , Oryctes sinaicus ) and palm fronds borer ( Phonapta frontales ) but its population density were varied according to the study region but the Oryctes elegans was dominant species and the solar energy traps was the best kind of traps which used in attracting palm stalk borer adults.